Pelatihan Pengelolaan Lingkungan Hidup Sehat bagi Siswa Terdampak Gempa Cianjur - Rahayu, Ucu; Nurdin, Gusti; Setyawan, Danang Budi (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase the knowledge and awareness of students affected by the Cianjur earthquake regarding healthy environmental management, including how to wash hands properly, sorting waste, and managing organic waste into compost. The targets of this activity were students and teachers at SD Negeri Sukamaju 1 Cugenang. The method of implementing this community service used socialization and practice. The results of this service showed that teachers and students increased knowledge about how to wash hands properly, could manage waste so that less waste was disposed of, and could produce their fertilizer from household waste. It also led to increased awareness of a healthy living environment in the environment of SD Negeri Sukamaju 1 Cugenang and its surroundings.